Analisis Permasalahan yang Dialami oleh Anak Korban Perceraian Orang Tua Di Kota Medan - Tarigan, Nabiilah Husnaa Br.; Putra Sinaga, M.Harwansyah; Sari Aritonang, Padilah (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2023)
This research is based on the many cases of parental divorce in Medan City that cause problems for their children. The purpose of this study is to reveal the problems experienced by children victims of parental divorce in Medan City. This research uses a descriptive qualitative approach with case study research. The existing data was collected using observation and interview techniques. The analysis used in this research activity is Miles and Huberman's analysis, namely data reduction, data presentation, and conclusions. The research subjects in this research activity were 7 child victims of parental divorce in Medan City. The results of this study stated the problems experienced by children victims of parental divorce in Medan City, namely problems with their mental and physical health, inhibiting their growth and development, experiencing difficulties in overcoming problems that occur in themselves and their lives, and the emergence of problems related to the difficulty of building relationships between their parents and themselves. As a result of the problems experienced by divorce victims' children, they make themselves more independent and strong individuals in living their lives. Keywords: Children;Victims;Parents;Divorce